2009
DOI: 10.9775/kvfd.2009.1364
|View full text |Cite
|
Sign up to set email alerts
|

E Vitamininin Karadeniz Alabalığı (Salmo labrax) Damızlık Stoklarında Üreme Performansına Etkisi

Abstract: SummaryThis study was conducted to examine the effects of feeding diets, different dose of vitamin E contains, on female and male Black Sea trout's (Salmo labrax) reproductive performance. Broodfish were fed with dry feed contained 100 (control), 250, 500, 1000 mg kg -1 vitamin E. Milt volume, spermatozoid number, fecundity and egg size were determined. Milt volume and sperm number were positively affected at a dose of 250 and 500 mg kg -1 vitamin E in the diet. A similar positive trend was also observed at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Our results show that an OO-containing diet inhibited ovarian development in female tilapia to a certain extent, but VE supplementation at 200 mg/kg in the OO-containing diet increased the GSI and the number of stage III and IV oocytes. In other studies, appropriate VE supplementation was shown to promote the reproductive performance of red swordtail ( Xiphophorus helleri ) [ 16 ] and Black Sea trout ( Salmo labrax ) [ 17 ]. The results of our study suggest that VE at 70 mg/kg in the OO-containing diet was sufficient to meet the growth requirements of female tilapia, but insufficient to meet the demands for ovarian development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that an OO-containing diet inhibited ovarian development in female tilapia to a certain extent, but VE supplementation at 200 mg/kg in the OO-containing diet increased the GSI and the number of stage III and IV oocytes. In other studies, appropriate VE supplementation was shown to promote the reproductive performance of red swordtail ( Xiphophorus helleri ) [ 16 ] and Black Sea trout ( Salmo labrax ) [ 17 ]. The results of our study suggest that VE at 70 mg/kg in the OO-containing diet was sufficient to meet the growth requirements of female tilapia, but insufficient to meet the demands for ovarian development.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of dietary VE can also positively affect animal reproduction. For example, dietary VE was shown to promote ovarian development, improve the spawning rate, and increase larval quality in red swordtail ( Xiphophorus helleri ) [ 16 ] and Black Sea trout ( Salmo labrax ) [ 17 ]. In addition, VE plays a vital role in the regulation of lipid metabolism and a deficiency of VE in the diet has been found to result in abnormal lipid deposition in fish [ 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%